2021
DOI: 10.3390/su13073800
|View full text |Cite
|
Sign up to set email alerts
|

Greening the Brownfields of Thermal Power Plants in Rural Areas, an Example from Romania, Set in the Context of Developments in the Industrialized Country of Germany

Abstract: This paper describes the greening of ash dumps from two thermal power plants located in Romania, in the villages of Mintia and Doicești, two rural areas neighboring middle-sized cities, both with architectural, archaeological and landscape heritage. Currently, the two Romanian villages have different fates in the context of shrinking cities, and solutions from the industrialized country of Germany that are more advanced in closing polluting thermal power plants are examples of this. Thus, the greening of indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The cultivation of non-food energy crops on marginal land sites like closed landfills, is an idea aimed at generating revenue from the biomass and biofuels produced from energy crop plantation [28,29,65]. At the same time, this course can contribute to phytoremediation of the land, aesthetic development, and microclimate moderation, in addition to covering some costs of post-closure maintenance and aftercare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivation of non-food energy crops on marginal land sites like closed landfills, is an idea aimed at generating revenue from the biomass and biofuels produced from energy crop plantation [28,29,65]. At the same time, this course can contribute to phytoremediation of the land, aesthetic development, and microclimate moderation, in addition to covering some costs of post-closure maintenance and aftercare.…”
Section: Discussionmentioning
confidence: 99%
“…This is in addition to providing potential ecosystem services like soil phytoremediation, aesthetic enhancements, micro-climate and environment moderation [20]. This strategy is however not restricted to landfill sites but can be equally applied to marginal and degraded lands that are otherwise classified as wastelands [28,29].…”
Section: Landfill Situation In South Asiamentioning
confidence: 99%
“…The Rheinelbe Gelsenkirchen forest park is part of the "Industrial Forest Ruhr Area" project, whose origins date back to the International Exhibition Budowlana (IBA) Emscher Park (1989-1999)-then still under the name of the "Residual Area Project". At the time of IBA [31], due to the structural changes in the Ruhr area, there was a great need to develop a concept for the re-use of 10,000 hectares of abandoned industrial land with little availability of financial resources [32]. The urban forest project aims, inter alia, to increase the share of forests in inner-city areas, while enabling natural processes of succession, bioretention and the availability of recreational areas.…”
Section: Discussion-studies On Industrial Transformation Inmentioning
confidence: 99%
“…That is the case with man-made innovative materials like textile layers used in green covers, supporting vegetation stratification and brownfield recovery, such as the two types of geotextiles, of which some are biodegradable and others are non-biodegradable. The biodegradable geotextiles are good for greening hills [43] and the non-biodegradable geotextiles are good for green walls [44,45], but if nutrients and water are not enough or maintenance is not conducted appropriately, the plants die (as in the case of the Sofitel Hotel in Vienna). This was personally observed in successive visits by the authors, as it will be shown in Section 3.3.…”
Section: Literature Reviewmentioning
confidence: 99%